2011
DOI: 10.1007/s11325-011-0593-y
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and the metabolic syndrome in an elderly healthy population: the SYNAPSE cohort

Abstract: In elderly subjects, the association between OSA and MetS was stronger for hyperglycemia and hypertension. Among factors explaining this association, hypoxemia appears to be the most important factor without any effect of indices of sleep fragmentation, sleep duration, and sleepiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…(26) In addition, this effect of IH was not exacerbated by daytime sleepiness or sleep duration in the French SYNAPSE cohort. (27) Recurrent nocturnal hypoxaemia and frequent arousals from SF may cause the HPA axis to lose the ability to respond to chronic recurring stress. Nocturnal hypercortisolism accompanied by low morning cortisol level was found in severe OSA subjects, who had higher insulin resistance when compared to controls.…”
Section: Pathophysiologymentioning
confidence: 99%
“…(26) In addition, this effect of IH was not exacerbated by daytime sleepiness or sleep duration in the French SYNAPSE cohort. (27) Recurrent nocturnal hypoxaemia and frequent arousals from SF may cause the HPA axis to lose the ability to respond to chronic recurring stress. Nocturnal hypercortisolism accompanied by low morning cortisol level was found in severe OSA subjects, who had higher insulin resistance when compared to controls.…”
Section: Pathophysiologymentioning
confidence: 99%
“…We included health insurance status in the model because it could be hypothesized that persons with health insurance might be more likely to visit a physician and be diagnosed as having obstructive sleep apnea should they experience it (30). Moreover, as reported in studies of non–war-exposed people, obstructive sleep apnea related to psychosomatic disorders and mental disorders, including headache, migraine, fatigue, and depression (31–33). To our knowledge, this is the first time that this possible mechanism has been demonstrated in a random sample of ethnically and culturally comparable immigrants to the same host country.…”
Section: Discussionmentioning
confidence: 84%
“…A recent study from France followed 806 elderly subjects over 7 years and found an independent association between sleep apnea and metabolic syndrome, even after correcting for age, gender and obesity [11] . A prospective study from Japan that spanned five years, examined nocturnal oximetry in over 4000 patients and calculated that a multivariable-adjusted hazard ratio (95% CI) for developing type 2 diabetes was 1.69 (1.04-2.76) among those with moderate to severe nocturnal intermittent hypoxia [12] .…”
Section: Epidemiologymentioning
confidence: 99%
“…OSA has been independently associated with hypertension and cardiovascular disease [2] . A high prevalence rate is being increasingly recognized, particularly in patients with metabolic syndrome, and several studies have suggested an independent association between OSA and insulin resistance (IR) and glycemic control [3][4][5][6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%